Chin Tuck Against Resistance (CTAR) and Shaker Exercise in Managing Swallowing Disorders (Dysphagia) in Patients with Non-Hemorrhagic Stroke - Puspita Sari, Nengke; Sari, Maritta (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2025)
Non-hemorrhagic stroke occurs due to obstruction of blood vessels, resulting in reduced blood flow to brain tissue. This condition may be caused by cerebral thrombosis, atherosclerosis, and cerebral embolism, which lead to vascular blockage as a result of plaque formation and subsequent narrowing of the vessels. These events can damage the cranial nerves responsible for regulating swallowing function, thereby causing dysphagia. Methods: This study employed a quasi-experimental design with a one-group pre–post test approach. A total of 10 respondents participated in the study. The sampling technique used was purposive sampling. Respondent information was collected through interviews and observation, while dysphagia assessment was performed through direct evaluation. Data were analyzed using the dependent t-test with a significance level of α = 0.05. Results and Discussion: There was a significant difference in dysphagia status before and after the intervention (p-value = 0.000). Conclusion: The Chin Tuck Against Resistance (CTAR) technique and Shaker Exercise are effective in managing swallowing disorders (dysphagia).